Restoring the financial sector and corporate deleveraging in Slovenia - Sila, Urban (OECD Economics Department Working Papers, 2015)
Excessive credit growth, poor risk assessment and lax lending standards in the run up to the 2008 global crisis led to unsustainable debt build-up in banks and related corporates. A weak framework for the governance of largely state-owned banks is likely to have contributed to the misallocation of credit. Furthermore, there were weaknesses in the banks' risk management systems and banks often didn't properly adhere to regulations and guidance given by the supervisor. Following the results of the stress tests and the Asset Quality Review, in December 2013, the major state-owned banks were recapitalised at a cost of around 11% of GDP, and part of their non-performing loans (NPLs) transferred to the Bank Asset Management Company (BAMC). Banks nevertheless remain weak, with still high NPLs, and corporations are highly leveraged. For successful restructuring and liquidation of assets, BAMC needs to act independently, transparently, with corporate governance of highest standards. Privatisation can improve corporate governance and closer supervision can ensure better compliance by banks. Insolvency legislation was thoroughly reformed in 2013 and should be implemented effectively to help return the healthy parts of the economy to invest and grow again. This Working Paper relates to the 2015 OECD Economic Survey of Slovenia (www.oecd.org/eco/surveys/economic-survey-slovenia.htm)